(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The present paper deals with selected sociolinguistic aspects of translation of The Laws of the Game from English into Polish. Particular attention was drawn to the importance of football in the contemporary world from the perspective of sport sociology. The authors addressed also the language of sport and described its most distinctive characteristics. The results of the analysis suggest that the main reason for the translation of The Laws of the Game containing translation mistakes is not only the insufficient experience and background knowledge of its translators but also the pressure of time.